Dental trauma in childhood: A literature review - Uchôa, Sue Ann Castro Lavareda; Corrêa, Suelen Castro Lavareda; Corrêa, Davi Lavareda; Corrêa, Vânia Castro (Seven Editora, 2024)
Dental trauma is a frequent incident in early childhood, categorized by the World Health Organization (WHO) as a public health problem, ranging from small cracks in the enamel to permanent tooth loss. The purpose of this study is to review the literature on the aspects of dental trauma in the primary dentition. Trauma to primary teeth occurs in preschool children and is often linked to behavioral characteristics, such as curiosity and restlessness, leading children to explore environments that are conducive to falls, resulting in an increased incidence of injuries. Success in post-traumatic treatment is directly associated with the provision of emergency care at the time of the incident. The delay in care can lead to a series of complications, depending on the type of trauma suffered by the tooth. In view of this perspective, in order to avoid complications resulting from trauma and delay in treatment, there are specific protocols and guidelines that can be employed. Each treatment approach is targeted at a specific type of trauma. In addition, in more severe cases, when there is severe trauma, a multidisciplinary treatment should be considered. DOI:https://doi.org/10.56238/sevened2023.007-075